Augmented reality applications in construction productivity: A systematic literature review - Xu Z; Feng Z; Babaeian Jelodar M; Guo BHW (Elsevier Ltd, 2024)
Augmented reality (AR) has been extensively researched for its applications in the construction industry. However, there is limited focus on its effects on productivity. This paper aims to bridge the gap by using a systematic literature review to investigate AR applications in the planning, design, and construction phases, focusing on their mechanisms for enhancing productivity. The paper classifies AR applications by their target construction tasks, features, and factors contributing to improved productivity. Additionally, it proposes a framework for prototyping AR applications and evaluating their effects on productivity. Key findings reveal several contributions: the need for further investigation of AR for positioning and hazard notification tasks; the utilisation of different augmentation methods, display tools, and tracking methods based on specific construction tasks; AR's positive impact on productivity in design review, discrepancy check, assembly, and hazard notification, while future research on evaluating productivity in progress management, planning simulation, and positioning.
Keywords: Augmented reality; Mixed reality; Construction productivity; Civil engineering; Digital technology